2001
DOI: 10.1007/s001250051580
|View full text |Cite
|
Sign up to set email alerts
|

Distinct long-term regulation of glycerol and non-esterified fatty acid release by insulin and TNF-α in 3T3-L1 adipocytes

Abstract: The regulation of adipocyte lipolysis is increasingly recognized to play a part in the pathophysiology of obesity, insulin resistance and Type II (non-insulindependent) diabetes mellitus. Both non-esterified fatty acids (NEFA) and glycerol, the two end products of lipolysis, are potential mediators for metabolic (dys)regulation, which is associated with these common conditions [1,2]. Prolonged increases in NEFA concentrations could induce or aggravate skeletal muscle insulin resistance [3], impair pancreatic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
31
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 34 publications
8
31
0
1
Order By: Relevance
“…This is the first report to address the long-term effects of insulin on human adipocyte lipid metabolism, and our findings are consistent with clinical observations of the association of hyperinsulinemia with increased lipolytic rate and fat accumulation in type 2 diabetes (4,21). Our findings are also consistent with previous studies investigating the effect of both chronic high insulin and glucose on mature rat adipocytes and differentiated 3T3-L1 adipocytes (7,25). These studies demonstrate that the combination of chronic high glucose and insulin stimulates lipolysis, which is in contrast to previous studies that have examined the acute effects by insulin (4,(21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…This is the first report to address the long-term effects of insulin on human adipocyte lipid metabolism, and our findings are consistent with clinical observations of the association of hyperinsulinemia with increased lipolytic rate and fat accumulation in type 2 diabetes (4,21). Our findings are also consistent with previous studies investigating the effect of both chronic high insulin and glucose on mature rat adipocytes and differentiated 3T3-L1 adipocytes (7,25). These studies demonstrate that the combination of chronic high glucose and insulin stimulates lipolysis, which is in contrast to previous studies that have examined the acute effects by insulin (4,(21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…The present study confirmed that rosiglitazone increases the response of WAT lipolysis to the inhibitory action of insulin [4]. It is worth noting that the inhibitory effect of insulin on NEFA was stronger than that on glycerol release, because of its additive effect on NEFA re-esterification to triglycerides [36,37]. Despite the stronger antilipolytic effect of insulin on WAT lipolysis, explants of rosiglitazone-treated rats exposed to insulin concentrations approximating those found in vivo under fasting and postprandial conditions maintained a higher rate of NEFA release than controls.…”
Section: Discussionsupporting
confidence: 86%
“…Notably, insulin did not affect the kinetics of glycerol release in JNK-intact cells over a 120 min period, but increased glycerol release in JNK1-and JNK2-deficient cells at 120 min. Although both the acute and chronic stimulatory effects of insulin on adipocyte glycerol release have been demonstrated [39,40], this is the first report that JNK1-or JNK2-deficiency increases the stimulatory effect of insulin on glycerol release and that JNK1/JNK2-deficiency is more important in the regulation of lipolysis than insulin.…”
Section: Discussionmentioning
confidence: 80%